Study of social tensions with government positions in national security - Belay, S. V.; Lisitsin, V. E. (Honor and Law, 2019)
The analysis of the nature of the category of social tension. The basic variants of interpretation of the definition of social tensions and the definition given to the position of public administration. Formed a model of social tensions and the impact on the state of the national security of the socio-economic basis. The necessity of using GIS technology to analyze statistics and trends of the social crisis.